Continuity of lower envelopes. (3rd July 2017) - Göğüş, Nihat Gökhan
Abstract: The purpose of the paper is to give a complete characterization of the continuity of lower envelopes in the infinite dimensional spaces. The characterization of upper or lower semicontinuity of envelopes, when stated in the language of multifunctions, has a dual geometric character which depends on the upper or lower semicontinuity of the corresponding multifunction.